Sure fire - Higgins, Jack, 1929- (G.P. Putnam's Sons, 2007)
Resentful of having to go and live with their estranged father after the death of their mother, fifteen-year-old twins, Rich and Jade, soon find they have more complicated problems when their father is kidnapped and their attempts to rescue him involve them in a dangerous international plot to control the world's oil.